Who are the long-distance commuters? Patterns and driving forces in Sweden - Marianne Öhman; Urban Lindgren (Cybergeo)
The aim of this study is to explore the determinants of long-distance commuting as compared to shorter commuting distances. Long-distance commuters are defined as individuals with a Euclidean distance of 200 kilometres or more between their housing and work place coordinates. With the increase in dual-earner households, long-distance commuting has emerged as a mobility strategy to manage the growing distances between home and work places. The empirical analysis is based on a sample from a longitudinal micro database containing demographic, socio-economic and geographic information for the total Swedish population. The sample includes all individuals in gainful employment in the age group 19 to 64, with valid geographical coordinates of residence and work place in 1994. A binomial logit model is estimated to capture the effects of variables related to the individual, the kind of work and the labour market, the household, and the geographical context. The results of the analysis show that the long-distance commuter is more likely to be male, younger, have at least three years of university education, previous experience of long-distance commuting, a very low or a very high income, a spouse with a university degree, no children, and is less likely to live in a detached house. He/she is also more likely to live in a larger city or its hinterland and work within certain occupational sectors. Previous experience of long-distance commuting in particular turns out to have a strong positive effect on the probability of being a long-distance commuter. A concluding discussion on the mobility strategies and the lifestyle of long-distance commuters suggests the diversity of driving forces to be found in individual and household preferences, and structural factors.